Anaerobic biodegradation of MTBE in a field site above the Israeli Coastal Aquifer: evidence from δ13C compound‐specific isotope analysis. Issue 6 (18th March 2016) - Gafni, Almog; Rosenzweig, Ravid; Gelman, Faina; Ronen, Zeev
Abstract: BACKGROUND: The fuel additive, methyl tert‐butyl ether (MTBE), is one of the most frequently occurring groundwater pollutants worldwide. The present study focused on assessing microbial degradation of MTBE in groundwater below a gasoline station situated above the Israeli Coastal Aquifer. Groundwater was monitored in six monitoring wells over a time period of 2.5 years. RESULTS: The site water geochemistry indicated that anaerobic conditions prevailed in two of the most contaminated wells. During a year MTBE concentrations declined from 81 to 4.2 mg L −1, concurrently, with a significant change in δ 13 C from −31.4 to −11.8 ‰ in a source area monitoring well. MTBE biodegradation during microcosm experiments under sulfate reducing and methanogenic conditions resulted in carbon isotopic enrichment factors ( ε ) of −17.2 ± 1.1 ‰. CONCLUSION: Significant decrease in MTBE concentrations, along with pronounced changes in carbon isotope composition, indicates in situ degradation of MTBE occurring at the site. This evidence was supported by a microcosm experiment with indigenous microbial cultures. The estimated rate of biodegradation is 0.7 year −1, which is about 70% of the total natural attenuation (NA) processes. © 2016 Society of Chemical Industry